# Solve for b -4/5b-6=-14 -45b-6=-14
Simplify each term.
Combine b and 45.
-b⋅45-6=-14
Move 4 to the left of b.
-4b5-6=-14
-4b5-6=-14
Move all terms not containing b to the right side of the equation.
Add 6 to both sides of the equation.
-4b5=-14+6
-4b5=-8
-4b5=-8
Multiply both sides of the equation by -54.
-54⋅(-4b5)=-54⋅-8
Simplify both sides of the equation.
Simplify -54⋅(-4b5).
Cancel the common factor of 5.
Move the leading negative in -54 into the numerator.
-54⋅(-4b5)=-54⋅-8
Move the leading negative in -4b5 into the numerator.
-54⋅-4b5=-54⋅-8
Factor 5 out of -5.
5(-1)4⋅-4b5=-54⋅-8
Cancel the common factor.
5⋅-14⋅-4b5=-54⋅-8
Rewrite the expression.
-14⋅(-4b)=-54⋅-8
-14⋅(-4b)=-54⋅-8
Cancel the common factor of 4.
Factor 4 out of -4b.
-14⋅(4(-b))=-54⋅-8
Cancel the common factor.
-14⋅(4(-b))=-54⋅-8
Rewrite the expression.
-1⋅(-b)=-54⋅-8
-1⋅(-b)=-54⋅-8
Multiply.
Multiply -1 by -1.
1⋅b=-54⋅-8
Multiply b by 1.
b=-54⋅-8
b=-54⋅-8
b=-54⋅-8
Simplify -54⋅-8.
Cancel the common factor of 4.
Move the leading negative in -54 into the numerator.
b=-54⋅-8
Factor 4 out of -8.
b=-54⋅(4(-2))
Cancel the common factor.
b=-54⋅(4⋅-2)
Rewrite the expression.
b=-5⋅-2
b=-5⋅-2
Multiply -5 by -2.
b=10
b=10
b=10
Solve for b -4/5b-6=-14

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top